2020
DOI: 10.5194/acp-20-4523-2020
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric energy budget response to idealized aerosol perturbation in tropical cloud systems

Abstract: Abstract. The atmospheric energy budget is analysed in numerical simulations of tropical cloud systems to better understand the physical processes behind aerosol effects on the atmospheric energy budget. The simulations include both shallow convective clouds and deep convective tropical clouds over the Atlantic Ocean. Two different sets of simulations, at different dates (10–12 and 16–18 August 2016), are simulated with different dominant cloud modes (shallow or deep). For each case, the cloud droplet number c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 109 publications
(172 reference statements)
3
6
0
Order By: Relevance
“…As the simulation progresses the daily mean ERF becomes increasingly positive due to an increasing LW component, driven by enhanced ice, which results in a positive ERF ARI and ERF ACI . A positive ERF ACI due to the ice phase response was also reported by Dagan et al (2020). By day 5 the ERF is close to 10 Wm −2 , driven predominantly by a strong LW component of 13 Wm −2 .…”
Section: Toa Radiative Effectssupporting
confidence: 70%
See 1 more Smart Citation
“…As the simulation progresses the daily mean ERF becomes increasingly positive due to an increasing LW component, driven by enhanced ice, which results in a positive ERF ARI and ERF ACI . A positive ERF ACI due to the ice phase response was also reported by Dagan et al (2020). By day 5 the ERF is close to 10 Wm −2 , driven predominantly by a strong LW component of 13 Wm −2 .…”
Section: Toa Radiative Effectssupporting
confidence: 70%
“…We use the ICOsahedral Non-hydrostatic (ICON) modelling framework in a regional, limited-area, configuration; a full description and evaluation of the model is provided by Zängl et al (2015). This setup has been used in previous studies (Dagan et al, 2020;Klocke et al, 2017) to study clouds and ACI. The model domain, covering an area of ∼6 × 10 6 km 2 , is centered on the Amazon between longitudes 68°W-4°W and latitudes 15°S-3°N (Figure 1) on a triangular grid with a horizontal resolution of ∼1,500 m, which is able to represent convection without the need for sub-grid scale parameterizations of mid-level and deep convection (Klocke et al, 2017).…”
Section: Model Description and Setupmentioning
confidence: 99%
“…Koren et al (2008) report an increase in cloud fraction and taller convective clouds at small AOD perturbations, and Ten Hoeve et al ( 2011) reported similar behaviour with COTliquid. This is consistent with ACI-induced warm phase invigoration in shallow convection and in the warm base of deep convective cells (Marinescu et al, 2021;Koren et al, 2014;Seiki and Nakajima, 2014;Igel and van den Heever, 2021;Dagan et al, 2020), or through anomalous thermal buoyancy due to the fire itself (Zhang et al, 2019). The reduction in cloud top REice (Figure 7c and d) with AOD for high-IWP scenes suggests more cloud droplets are reaching the freezing level; this may due to ACI processes or enhanced aerosol activation through thermally-induced anomalous buoyancy, making attribution of the dominant mechanism difficult.…”
Section: Discussionsupporting
confidence: 79%
“…The increase of CF and TWP with N a in the tropics could be driven by local processes such as humidification of the troposphere (Abbott & Cronin, 2021; Dagan et al., 2020) and invigoration of convection (Altaratz et al., 2014). However, the increased tropical cloudiness under polluted conditions could also be driven by changes in the large‐scale conditions associated with the increase in N a in the sub‐tropics—effect which is not accounted for in the un‐coupled simulations, which demonstrate a weaker response (Figure 5).…”
Section: Resultsmentioning
confidence: 99%